Tertib manhaj penyelesaian mukhtalif al-ḥadīth menurut al-marbawi dalam baḥr al-mādhī - Mohd Solleh Ab Razak,; Roshimah Shamsudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The writing of Bahr al-Madhi by al-Marbawi which is the definitive work on hadith in the Malay realm had launched his name to prominence as a scholar who massively contributes to the sciences of hadith, particularly via commentaries on hadiths quoted in Jami’ al-Tirmidhi. Al-Marbawi in this work, presents a discussion on the solution to the apparent contradictions that occur among the hadiths which is termed as mukhtalif al-hadith. In spite of the prominence of the work, it is not devoid of commentaries, predominantly from the point of his mastery of the knowledge in the field of hadith. Thus, this study aims to examine the methods of al-Marbawi in interacting with mukhtalif al-hadith in Bahr al Madhi specifically from the viewpoint of the sequence of the solutions. Therefore, a qualitative study through content analysis design was conducted for data collection and analysis process. The study finds that the sequence of methods of mukhtalif al-hadith practised by al-Marbawi is to precede al-nasakh al-sarikh, followed by al-jam‘, al-naskh ghayr al-sarih, al-tarjih and al-tawaqquf. This sequence is found to be in line with the approach of the majority of other hadith scholars. Additionally, al-Marbawi is found to not only citing the views of scholars on issues relating to al-mukhtalif al-hadith but he also criticizes the solutions that do not adhere to the sequence of the methodology, erroneous takwil, and claims of al-nasakh. The findings provide a clearer picture of the authority of al-Marbawi’s knowledge in questions pertaining to mukhtalif al-hadith.